Environment-friendly, low-cost and recyclable large-scale synthesis method of ZIF-67 material and method thereof
By using industrial-grade raw materials and additives to adjust the alkalinity of tap water, the environmentally friendly, inexpensive, and large-scale synthesis of ZIF-67 material has been achieved, solving the problems of low yield and high cost in existing technologies, making it suitable for industrial applications.
Patent Information
- Application Number
- CN202411373745.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-29
AI Technical Summary
Existing methods for synthesizing ZIF-67 materials suffer from problems such as low yield, use of large amounts of organic solvents and energy waste, complex operation and high cost, which limit their large-scale synthesis.
Industrial-grade cobalt chloride hexahydrate and industrial-grade 2-methylimidazole were used as raw materials. After being stirred evenly in tap water, the mixture was allowed to stand, centrifuged, washed, and dried. The alkalinity was adjusted using n-butylamine. The waste liquid was recycled through a large-scale synthesis method under room temperature and atmospheric pressure conditions.
The synthesis of ZIF-67 material with high yield, low cost, and environmental friendliness has been achieved. The material has uniform particle size and high crystallinity, making it suitable for large-scale industrial production and reducing environmental pollution and resource waste.
Smart Images

Figure CN119285970A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of large-scale synthesis of metal organic frameworks, and particularly relates to an environmentally friendly, low-cost, recyclable method for large-scale synthesis of ZIF-67 materials. Technical Background
[0002] In the past two decades, metal organic frameworks (MOFs), as emerging porous materials assembled from metal ions / clusters and organic ligands, have attracted great interest from researchers. [Fang Ruiqi. Research on the catalytic conversion of biomass furan platform molecules by metal organic framework-based composite materials [D]. South China University of Technology, 2019.] Compared with traditional porous materials, MOFs have the following advantages: (1) Structural diversity. By adjusting the types of metals and organic ligands, MOFs materials with various structures can be prepared. (2) High specific surface area and porosity. This gives MOFs materials unique advantages in the fields of catalysis and gas adsorption. (3) Adjustable material morphology and pore structure. The morphology and pore structure of MOFs materials can be adjusted according to the geometric structure of organic ligands and the coordination mode with metal ions / clusters. (4) Contains unsaturated metal sites. During the assembly process, a large number of metal unsaturated sites are usually exposed as catalytic active centers. (5) The preparation process is relatively simple.
[0003] Zeolitic imidazolate framework materials (ZIFs) are a new type of metal organic framework (MOFs) material composed of transition metal cations (M) and organic imidazolate linkers (Im). When the metal (M) component is bridged with the ligand and the edge of M-Im-M is located at 145°, the structure of ZIFs is formed, which is similar to Si-O-Si in conventional silica-based zeolites. Since 2010, Yaghi et al. reported the synthesis and structure of ZIFs, and a large number of studies have been devoted to its research and application, such as catalysis, adsorption and sensing. ZIF-67 is a representative structure composed of Co 2+It is coordinated with 2-methylimidazole and has a sodalite framework (SOD) topological structure. ZIF-67 has excellent microporous structure, high surface area and adjustable pore structure, and most of them show excellent thermal stability and chemical stability. Therefore, it has a wide range of applications in gas adsorption, molecular separation, electrochemistry, catalysis, etc. [Zhong G., Liu D. and Zhang J. The application of ZIF-67 and its derivatives: adsorption, separation, electrochemistry and catalysts [J]. Journal of Materials Chemistry A, 2018, 6 (5): 1887-1899.] However, these applications are cost-sensitive. If ZIF-67 materials can be synthesized at low cost using energy and raw materials and effective synthesis methods, it is more likely to improve the utilization value of ZIF-67 materials.
[0004] At present, the method for synthesizing ZIF-67 material has hydrothermal method, solvothermal method, microwave assisted method, sonochemical method and supercritical CO2 method etc., among which hydrothermal method and solvothermal method are the most common. These methods not only waste a large amount of energy, but also are not environmentally friendly, which limits the large-scale synthesis of ZIF-67 material to a great extent. For example, hydrothermal method and solvothermal method have large energy consumption, causing waste of resources, and organic solvent is expensive in solvothermal method, and potential pollution can also be caused to the environment. For example, CN110813245A microwave assisted method and CN112358623A supercritical CO2 method can prepare ZIF-67 material of uniform size, consuming less time, and environmental pollution is small, but there are problems such as complicated preparation process, harsh conditions, and high cost. [Qian J., Sun F. and Qin L. Hydrothermal synthesis of zeolitic imidazolate framework-67 (ZIF-67) nanocrystals [J]. Materials Letters, 2012, 82 (220-223).] Recently, Qian et al. synthesized imidazolate framework zeolite ZIF-67 nanocrystals in pure water at room temperature, which is green, energy-saving and easy to operate, but also has the disadvantages of low yield and poor morphology. Therefore, from the perspective of green, environmental protection and economic cost, it is of great significance to develop an environmentally friendly, low-cost and recyclable method for large-scale synthesis of ZIF-67 materials. Summary of the invention
[0005] In view of the problems of the prior art, the purpose of the present invention is to provide an environmentally friendly, low-cost, recyclable method for large-scale synthesis of ZIF-67 materials, so as to solve the problems of low yield, use of large amounts of organic solvents and energy waste, complex operation, harsh conditions, high cost, etc. in the existing ZIF-67 synthesis method.
[0006] The invention provides an environmentally friendly, low-cost and recyclable method for large-scale synthesis of ZIF-67 materials. The method uses industrial-grade cobalt chloride hexahydrate and industrial-grade 2-methylimidazole as raw materials, n-butylamine as an additive, and tap water as a solvent. The raw materials are mixed and stirred evenly under room temperature and normal pressure conditions, and then the mixture is allowed to stand for a period of time at room temperature to obtain a precipitation layer. The precipitate is centrifuged, washed, dried, and the like to obtain a purple ZIF-67 powder.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A method for large-scale synthesis of ZIF-67 materials that is environmentally friendly, low-cost and recyclable comprises the following steps:
[0009] (1) Add 2-methylimidazole to tap water, stir to fully dissolve it, then add n-butylamine and stir to obtain solution A, measure the pH of solution A (>10.3), and stop stirring after the value stabilizes;
[0010] (2) adding cobalt chloride hexahydrate into tap water and stirring to fully dissolve it to obtain solution B;
[0011] (3) adding solution B to solution A and stirring evenly to obtain a turbid solution C;
[0012] (4) The turbid solution C is allowed to stand at room temperature for a period of time to obtain a precipitate layer, and the precipitate is centrifuged, washed, and other operations are performed to obtain a product. The product is vacuum dried to obtain a purple powdery ZIF-67 material.
[0013] (5) Take the supernatant above the precipitation layer in step (4), quantify the dimethylimidazole content in the supernatant by GC / MS internal standard method, add a certain amount of dimethylimidazole, stir to fully dissolve it, then add a certain amount of n-butylamine and stir evenly to obtain solution A, so that the pH value of solution A is >10.3, and continue to repeat steps (1)(2)(3)(4) at room temperature to obtain a purple powdery ZIF-67 material.
[0014] Furthermore, the stirring in step (1) and step (2) is carried out at room temperature, and the cobalt chloride hexahydrate and dimethylimidazole are of industrial grade.
[0015] Furthermore, the mass concentration of 2-methylimidazole in the solution A of step (1) is 14-15.5 g / L; the molar concentration of n-butylamine is 0.15-0.25 mol / L, and the pH of the solution A is stabilized in the range of 10.6-11.6.
[0016] Furthermore, the mass concentration of cobalt chloride hexahydrate in the solution B in step (2) is 35 to 57 g / L.
[0017] Furthermore, in the mixed solution of step (3), the molar ratio of cobalt chloride hexahydrate, dimethylimidazole, n-butylamine and water is 1:5:(4.5-6):1851; the stirring speed when the solution A and the solution B are mixed is 200 r / min, and the stirring time is 5 min-1 h.
[0018] Furthermore, in step (4), the operation of allowing solution C to stand is carried out at room temperature for 24 hours; the washing is carried out with deionized water; the centrifugal speed is 4000 r / min for 2 minutes; and the drying is vacuum drying at 100° C. for 12 hours.
[0019] Furthermore, in step (5), the mass concentration of 2-methylimidazole in the supernatant determined by GC / MS internal standard method is 5.5-6.5 g / L; the amount of n-butylamine added is 500 mL. The pH of solution A is stabilized in the range of 10.6-10.7.
[0020] Furthermore, the ZIF-67 material prepared by the above steps has a particle size of 4 to 6 μm and a specific surface area of 1300 to 1400 m 2 / g, pore volume is 0.55~0.60cm 3 / g.
[0021] Compared with the prior art, the present invention has the following advantages or effects:
[0022] (1) The present invention is easy to operate and has simple conditions. During the synthesis process, it is only necessary to fully dissolve the cobalt salt solution and the dimethylimidazole solution, and then continue to stir the mixture for a period of time to obtain the ZIF-67 material. Except for the vacuum drying step, the rest are carried out at room temperature, which consumes less energy than other technologies, and has the advantages of energy saving, low cost and high efficiency.
[0023] (2) The solvent used in the present invention is tap water. Most of the traditional methods use organic solvents to prepare ZIF-67 materials, which are toxic, harmful, difficult to handle, and cause certain pollution to the environment. Tap water has the advantages of being cheap, easy to obtain, and pollution-free to the environment, and is the best choice for a green ideal solvent.
[0024] (3) The present invention uses industrial-grade cobalt chloride hexahydrate as a cobalt source and industrial-grade 2-methylimidazole as an organic ligand, which greatly reduces the cost of raw materials and is conducive to industrial mass synthesis. Among all cobalt salts, the price of the cobalt chloride hexahydrate used is relatively cheap and has little pollution to the environment. In exploring the influence of the type of cobalt salt, cobalt chloride hexahydrate as a cobalt salt is conducive to the formation of regular, uniform rhombic dodecahedron ZIF-67 materials. It is reported that most methods for preparing ZIF-67 materials have a molar ratio of ligand to cobalt salt of 8:1, or even a higher molar ratio for synthesis. In the present invention, a molar ratio of ligand to cobalt salt of 5:1 is used, which is conducive to forming a more uniform morphology, and also reduces the preparation cost to a certain extent, avoiding the waste of organic ligands.
[0025] (4) The present invention uses n-butylamine as an additive to play a deprotonating role, greatly improving the yield of the product. In the past, the synthesis of ZIF-67 materials under pure water at room temperature not only required the use of a large amount of organic ligands to prepare, but also had a low yield and might obtain a non-porous and dense Dia structure. With n-butylamine as an additive, the higher alkalinity can deprotonate the intermediate species, thereby affecting the nucleation and growth rates, greatly improving the yield of the synthesized ZIF-67 material (close to 99%), and has little effect on the morphology and structure of the ZIF-67 material under appropriate alkalinity. In addition, the waste liquid obtained after the large-scale synthesis of ZIF-67 materials can be recycled and reused, reducing the cost of raw materials and waste liquid treatment, and reducing pollution.
[0026] (5) The present invention provides an environmentally friendly, low-cost, and recyclable method for large-scale synthesis of ZIF-67 materials. By adjusting the amount of n-butylamine added to adjust the alkalinity in a room temperature water environment, not only the morphology is adjusted to obtain a ZIF-67 material with large particle size, relatively uniformity, and high crystallinity, but also the yield of the synthesized ZIF-67 material is greatly improved. By adjusting the formulation parameters of different multiples, the synthesis is enlarged step by step, a large amount of synthesis is performed at a high multiple and the mother liquor is circulated three times, and the verification of the synthesis experiment of kilogram-level ZIF-67 materials is completed.
[0027] In summary, the present invention has the advantages of simple operating conditions, low pollution, energy saving, recyclability, and low cost. The synthesis process is carried out at room temperature, with tap water as the solvent, which is cheap, easy to obtain, and pollution-free to the environment; the cobalt salts and organic ligands used are all industrial grade, which greatly reduces the cost of preparation; the waste liquid after the reaction of this method can be recycled, realizing the resource utilization of "turning waste into treasure". The present invention synthesizes a large amount of ZIF-67 materials at a high multiple and circulates the mother liquor three times to complete the verification of the synthesis experiment of kilogram-level ZIF-67 materials. The synthesized ZIF-67 material is relatively uniform and has a high degree of crystallinity, which is suitable for industrial large-scale synthesis. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 XRD patterns of ZIF-67 materials prepared in Examples 1 and 2;
[0029] Figure 2 This is a SEM image of the ZIF-67 material prepared in Example 1;
[0030] Figure 3 This is the SEM image of the ZIF-67 material prepared in the first cycle in Example 2;
[0031] Figure 4 This is the SEM image of the ZIF-67 material prepared in the second cycle in Example 2;
[0032] Figure 5 This is the SEM image of the ZIF-67 material prepared in the third cycle in Example 2;
[0033] Figure 6 TGA graph of ZIF-67 materials prepared in Examples 1 and 2;
[0034] Figure 7 The XRD pattern of the ZIF-67 material prepared in Example 1 after heat treatment with Ar and air;
[0035] Figure 8 The XRD pattern of the ZIF-67 material prepared in Example 1 after being heat-treated in boiling water;
[0036] Fig. 9 N2 adsorption-desorption isotherm and pore size distribution curve of the ZIF-67 material prepared in Example 1. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but the implementation and protection scope of the present invention are not limited thereto.
[0038] Example 1
[0039] 492.0 g of 2-methylimidazole was added to 35.0 L of tap water, and stirred at 200 r / min for 10 min at room temperature to completely mix it, and then 530 mL of n-butylamine was added thereto and stirred for 5 min to completely mix it to obtain solution A; 285.6 g of cobalt chloride hexahydrate was added to 5.0 L of tap water, and stirred at 200 r / min for 10 min to completely dissolve it to obtain solution B; solution B was completely poured into solution A, and stirred at a stirring rate of 200 r / min for 1 h to obtain a turbid solution, which was allowed to stand for 24 h, and an obvious precipitation layer appeared; the precipitate was centrifuged and washed with deionized water, and vacuum dried at 100°C for 12 h to obtain purple ZIF-67 powder.
[0040] Example 2
[0041] Take 35.0L of the supernatant in Example 1, add 292.0g of 2-methylimidazole thereto, stir at a rate of 200r / min for 10min at room temperature to completely mix it, then add 500mL of n-butylamine and continue stirring for 5min to completely mix it to obtain solution A; weigh 285.6g of cobalt chloride hexahydrate and add it to 5.0L of tap water, stir at a rate of 200r / min for 10min to completely dissolve it to obtain solution B; pour solution B completely into solution A, stir at a stirring rate of 200r / min for 1h to obtain a turbid solution, stand for 24h, and an obvious precipitation layer appears; centrifuge and wash the precipitate with deionized water, and vacuum dry it at a temperature of 100°C for 12h to obtain the first cycle of purple ZIF-67 powder. Repeat the same operation above to obtain the second cycle of purple ZIF-67 powder. Repeat the same operation above again to obtain the third cycle of purple ZIF-67 powder.
[0042] The ZIF-67 materials prepared in Examples 1 and 2 were used as representatives for analysis, and the analysis results of the ZIF-67 materials prepared in other Examples were basically the same as those in Example 1, and are not provided one by one.
[0043] (I) Crystal structure properties of large-scale synthesis of ZIF-67 materials
[0044] The crystal structure of the large-scale synthesized ZIF-67 material in Examples 1 and 2 of the present invention was characterized by using a D8-ADVANCE X-ray diffractometer produced by Bruker, Germany. Figure 1 The PDF standard card of ZIF-67 material and the wide-angle X-ray diffraction pattern of ZIF-67 material prepared in Examples 1 and 2 of the present invention. Figure 1 It can be seen that the ZIF-67 materials prepared in Examples 1 and 2 both showed strong characteristic diffraction peaks of the ZIF-67 metal organic framework, indicating that there is a high crystallinity ZIF-67 component in the product.
[0045] (II) Microstructural properties of large-scale synthesized ZIF-67 materials
[0046] The microstructure of the ZIF-67 material prepared in Examples 1 and 2 of the present invention was characterized using a Regulus 8100 scanning electron microscope. Figure 2 , Figure 3 , Figure 4 , Figure 5 As shown, the ZIF-67 materials prepared in Examples 1 and 2 both exhibited large-scale regular rhombic dodecahedron morphology, and the size was relatively uniform, with a particle size of 4 μm to 6 μm.
[0047] (III) Stability of large-scale synthesis of ZIF-67 materials
[0048] The thermal stability of the ZIF-67 materials prepared in Examples 1 and 2 of the present invention was characterized using a TG209F1 thermogravimetric analyzer. Figure 6 As shown, the prepared ZIF-67 material exhibits good thermal stability within 500°C.
[0049] The crystal structure of the ZIF-67 material after heating in Ar atmosphere, air atmosphere, and water in Example 1 was characterized using a D8-ADVANCE X-ray diffractometer produced by Bruker, Germany. Figure 7 , 8 As shown, the large-scale synthesized ZIF-67 material still showed strong characteristic diffraction peaks of the ZIF-67 metal organic framework within 10 hours of calcination at 400°C in Ar atmosphere, but could only maintain the crystal structure after calcination at 200°C for 10 hours in air; moreover, the ZIF-67 material still showed characteristic diffraction peaks of the ZIF-67 metal organic framework after being treated in boiling water for 5 days; these indicate that the ZIF-67 material prepared in Example 1 of the present invention has strong stability.
[0050] (IV) Specific surface area and pore properties of large-scale synthesis of ZIF-67 materials
[0051] The pore properties of the sample prepared in Example 1 of the present invention were characterized using an ASAP2460 specific surface area pore size distribution instrument produced by Micro Corporation of the United States, and the results are shown in Table 1. As can be seen from Table 1, the ZIF-67 material prepared in Example 1 of the present invention has a high specific surface area and pore volume.
[0052] Table 1
[0053] sample BET specific surface area (m2 / g) Pore volume (cm3 / g) ZIF-67 1402.2 0.545
[0054] Fig. 9 is the N2 adsorption-desorption isotherm of the ZIF-67 material prepared in Example 1 of the present invention, Fig. 9 It can be seen that the ZIF-67 material prepared in Example 1 of the present invention shows a type I adsorption isotherm, and the adsorption amount increases sharply at a pressure of P / P0<0.01, and combined with the results of the pore size distribution, it is shown that the sample has a microporous structure.
[0055] Example 3
[0056] 246.0 g of 2-methylimidazole was added to 17.5 L of tap water, and stirred at 200 r / min for 10 min at room temperature to completely mix it, and then 270 mL of n-butylamine was added thereto and stirred for 5 min to completely mix it to obtain solution A; 142.8 g of cobalt chloride hexahydrate was added to 2.5 L of tap water, and stirred at 200 r / min for 10 min to completely dissolve it to obtain solution B; solution B was completely poured into solution A, and stirred at a stirring rate of 200 r / min for 1 h to obtain a turbid solution, which was allowed to stand for 24 h, and an obvious precipitation layer appeared; the precipitate was centrifuged and washed with deionized water, and vacuum dried at 100°C for 12 h to obtain purple ZIF-67 powder.
[0057] Example 4
[0058] 123.0 g of 2-methylimidazole was added to 8.0 L of tap water, and stirred at 200 r / min for 10 min at room temperature to completely mix it, and then 130 mL of n-butylamine was added thereto and stirred for 5 min to completely mix it to obtain solution A; 71.4 g of cobalt chloride hexahydrate was added to 2.0 L of tap water, and stirred at 200 r / min for 10 min to completely dissolve it to obtain solution B; solution B was completely poured into solution A, and stirred at a stirring rate of 200 r / min for 40 min to obtain a turbid solution, which was allowed to stand for 24 h, and an obvious precipitation layer appeared; the precipitate was centrifuged and washed with deionized water, and vacuum dried at 100°C for 12 h to obtain purple ZIF-67 powder.
[0059] Example 5
[0060] 61.5 g of 2-methylimidazole was added to 4.0 L of tap water, and stirred at 200 r / min for 10 min at room temperature to completely mix it. Then 65 mL of n-butylamine was added thereto and stirred for 5 min to completely mix it to obtain solution A; 35.7 g of cobalt chloride hexahydrate was added to 1.0 L of tap water, and stirred at 200 r / min for 10 min to completely dissolve it to obtain solution B; solution B was completely poured into solution A, and stirred at a stirring rate of 200 r / min for 20 min to obtain a turbid solution, which was allowed to stand for 24 h, and an obvious precipitation layer appeared; the precipitate was centrifuged and washed with deionized water, and vacuum dried at 100°C for 12 h to obtain purple ZIF-67 powder.
[0061] Example 6
[0062] 12.3 g of 2-methylimidazole was added to 800 mL of tap water, and stirred at 200 r / min for 10 min at room temperature to completely mix it, and then 16.5 mL of n-butylamine was added thereto and stirred for 5 min to completely mix it to obtain solution A; 7.14 g of cobalt chloride hexahydrate was added to 200 mL of tap water, and stirred at 200 r / min for 10 min to completely dissolve it to obtain solution B; solution B was completely poured into solution A, and stirred at a stirring rate of 200 r / min for 10 min to obtain a turbid solution, which was allowed to stand for 24 hours, and an obvious precipitation layer appeared; the precipitate was centrifuged and washed with deionized water, and vacuum dried at 100°C for 12 hours to obtain purple ZIF-67 powder.
[0063] Example 7
[0064] 12.3 g of 2-methylimidazole was added to 800 mL of tap water, and stirred at 200 r / min for 10 min at room temperature to completely mix it, and then 16.5 mL of n-butylamine was added thereto and stirred for 5 min to completely mix it to obtain solution A; 7.47 g of cobalt acetate tetrahydrate was added to 200 mL of tap water, and stirred at 200 r / min for 10 min to completely dissolve it to obtain solution B; solution B was completely poured into solution A, and stirred at a stirring rate of 200 r / min for 10 min to obtain a turbid solution, which was allowed to stand for 24 hours, and an obvious precipitation layer appeared; the precipitate was centrifuged and washed with deionized water, and vacuum dried at 100°C for 12 hours to obtain purple ZIF-67 powder.
[0065] Example 8
[0066] 12.3 g of 2-methylimidazole was added to 800 mL of tap water, and stirred at 200 r / min for 10 min at room temperature to completely mix it, and then 13 mL of n-butylamine was added thereto and stirred for 5 min to completely mix it to obtain solution A; 8.73 g of cobalt nitrate hexahydrate was added to 200 mL of tap water, and stirred at 200 r / min for 10 min to completely dissolve it to obtain solution B; solution B was completely poured into solution A, and stirred at a stirring rate of 200 r / min for 10 min to obtain a turbid solution, which was allowed to stand for 24 hours, and an obvious precipitation layer appeared; the precipitate was centrifuged and washed with deionized water, and vacuum dried at 100°C for 12 hours to obtain purple ZIF-67 powder.
[0067] Example 9
[0068] 1.23 g of 2-methylimidazole was added to 80 mL of tap water, and stirred at 200 r / min for 10 min at room temperature to completely mix it, and then 2.0 mL of n-butylamine was added thereto and stirred for 5 min to completely mix it to obtain solution A; 0.714 g of cobalt chloride hexahydrate was added to 20 mL of tap water, and stirred at 200 r / min for 10 min to completely dissolve it to obtain solution B; solution B was completely poured into solution A, and stirred at a stirring rate of 200 r / min for 5 min to obtain a turbid solution, which was allowed to stand for 24 hours, and an obvious precipitation layer appeared; the precipitate was centrifuged and washed with deionized water, and vacuum dried at 100°C for 12 hours to obtain purple ZIF-67 powder.
[0069] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for large-scale synthesis of ZIF-67 materials that is environmentally friendly, low-cost and recyclable, characterized in that: It uses industrial grade cobalt chloride hexahydrate and industrial grade 2-methylimidazole as raw materials and tap water as solvent for preparation, and can recycle the waste liquid to achieve resource utilization; The specific steps include: (1) 2-methylimidazole was added to tap water, stirred to fully dissolve, and then n-butylamine was added and stirred to obtain a solution A. The pH of the solution A was measured to be greater than 10.3, and stirring was stopped after the value stabilized; (2) adding cobalt chloride hexahydrate into tap water and stirring to fully dissolve it to obtain solution B; (3) adding solution B to solution A and stirring evenly to obtain a turbid solution C; (4) The turbid solution C is allowed to stand at room temperature to obtain a precipitate, and the precipitate is centrifuged and washed to obtain a product, and the product is vacuum dried to obtain a purple powdery ZIF-67 material; (5) Take the supernatant above the precipitation layer in step (4), quantify the dimethylimidazole content in the supernatant by GC / MS internal standard method, add dimethylimidazole, stir to fully dissolve it, then add n-butylamine and stir evenly to obtain solution A, so that the pH value of solution A is >10.3, and continue to repeat steps (1)(2)(3)(4) at room temperature to obtain a purple powdery ZIF-67 material.
2. The environmentally friendly, low-cost, recyclable large-scale synthesis method of ZIF-67 material according to claim 1, characterized in that: In step (1) and step (2), the stirring is carried out at room temperature, and the cobalt chloride hexahydrate and dimethylimidazole are of industrial grade.
3. The environmentally friendly, low-cost, recyclable large-scale synthesis method of ZIF-67 material according to claim 1 is characterized in that: In step (1), the mass concentration of 2-methylimidazole in the solution A is 14-15.5 g / L; the molar concentration of n-butylamine is 0.15-0.25 mol / L, and the pH of the solution A is stabilized in the range of 10.6-11.
6.
4. The environmentally friendly, low-cost, recyclable large-scale synthesis method of ZIF-67 material according to claim 1, characterized in that: In step (2), the mass concentration of cobalt chloride hexahydrate in the solution B is 35-57 g / L.
5. The environmentally friendly, low-cost, recyclable large-scale synthesis method of ZIF-67 material according to claim 1 is characterized in that: In step (3), the molar ratio of cobalt chloride hexahydrate, dimethylimidazole, n-butylamine and water in the turbid solution C is 1:5:(4.5-6):1851; the stirring speed when the solution A and the solution B are mixed is 200-300 r / min, and the stirring time is 5 min-1 h.
6. The environmentally friendly, low-cost, recyclable large-scale synthesis method of ZIF-67 material according to claim 1, characterized in that: In step (4), the operation of allowing the turbid solution C to stand is carried out at room temperature for 16 to 24 hours.
7. The environmentally friendly, low-cost, recyclable large-scale synthesis method of ZIF-67 material according to claim 1, characterized in that: In step (4), the washing is performed with deionized water; the centrifugal speed is 4000-5000 r / min, and the time is 2-5 min; and the drying is performed at 80-100° C. in vacuum, and the drying time is 12-24 h.
8. The environmentally friendly, low-cost, recyclable large-scale synthesis method of ZIF-67 material according to claim 1, characterized in that: In step (5), the mass concentration of 2-methylimidazole in the supernatant determined by GC / MS internal standard method is 5.5-6.5 g / L; the amount of n-butylamine added is 500 mL; and the pH of solution A is stabilized in the range of 10.6-10.
7.
9. The ZIF-67 material prepared by the method according to any one of claims 1 to 8.
10. The ZIF-67 material according to claim 9, characterized in that: The ZIF-67 material has a particle size of 4 to 6 μm and a specific surface area of 1300 to 1400 m 2 / g, pore volume is 0.55~0.60cm 3 / g.
Citation Information
Patent Citations
Preparation method of nanometer-to-micrometer scale zeolitic imidazolate frameworks (ZIFs)
CN102731538A
Method for preparing zeolite imidazate framework material
CN105985362A
Green and economic large-scale synthesis method of ZIF-8 material
CN116041717A
Method for large-scale synthesis of Zn / Co-ZIF material at room temperature and normal pressure
CN118240232A
Method for producing zeolitic imidazolate framework (ZIF) crystals and coatings
WO2023232717A1